The Colony Stimulating Factor-1 Receptor (CSF-1R)-Mediated Regulation of Microglia/Macrophages as a Target for Neurological Disorders (Glioma, Stroke) - Barca, Cristina; Foray, Claudia; Hermann, Sven; Herrlinger, Ulrich; Remory, Isabel; Laoui, Damya; Schäfers, Michael; Grauer, Oliver M.; Zinnhardt, Bastian; Jacobs, Andreas H. (Frontiers in Immunology, 2021)
Immunomodulatory therapies have fueled interest in targeting microglial cells as part of the innate immune response after infection or injury. In this context, the colony-stimulating factor 1 (CSF-1) and its receptor (CSF-1R) have gained attention in various neurological conditions to deplete and reprogram the microglia/macrophages compartment. Published data in physiological conditions support the use of small-molecule inhibitors to study microglia/macrophages dynamics under inflammatory conditions and as a therapeutic strategy in pathologies where those cells support disease progression. However, preclinical and clinical data highlighted that the complexity of the spatiotemporal inflammatory response could limit their efficiency due to compensatory mechanisms, ultimately leading to therapy resistance. We review the current state-of-art in the field of CSF-1R inhibition in glioma and stroke and provide an overview of the fundamentals, ongoing research, potential developments of this promising therapeutic strategy and further application toward molecular imaging.